IGFBP6 regulates vascular smooth muscle cell proliferation and morphology via cyclin E–CDK2. Issue 12 (11th June 2020) - Wang, Zhecun; Qi, Yunling; Wang, Rui; Wu, Weibin; Li, Zilun; Wang, Mian; Liu, Ruiming; Zhang, Chunxiang; Li, Wen; Wang, Shenming
Abstract: Despite the high prevalence of varicose veins, the underlying pathogenesis of this disease remains unclear. The present study aims to explore the role of insulin‐like growth factor binding protein 6 (IGFBP6) in vascular smooth muscle cells (VSMCs). Using a protein array approach, we identified several differentially expressed proteins between varicose great saphenous veins and normal great saphenous veins. Bioinformatic analysis showed that IGFBP6 was closely related to cell proliferation. Further validation confirmed that IGFBP6 was one of the most highly expressed proteins in varicose vein tissue. Knocking down IGFBP6 in VSMCs significantly attenuated cell proliferation and induced the S phase arrest during the cell cycle. Further experiments demonstrated that IGFBP6 knockdown increased cyclin E ubiquitination, which reduced expression of cyclin E and phosphorylation of CDK2. Furthermore, IGFBP6 knockdown arrested centrosome replication, which subsequently influenced VSMC morphology. Ultimately, IGFBP6 was validated to be involved in VSMC proliferation in varicose vein tissues. The present study reveals that IGFBP6 is closely correlated with VSMC biological function and provides unprecedented insights into the underlying pathogenesis of varicose veins.